Reach Out Churches: A Community-Based Participatory Research Pilot Trial to Assess the Feasibility of a Mobile Health Technology Intervention to Reduce Blood Pressure Among African Americans. Issue 4 (July 2018) - Skolarus, Lesli E.; Cowdery, Joan; Dome, Mackenzie; Bailey, Sarah; Baek, Jonggyu; Byrd, James Brian; Hartley, Sarah E.; Valley, Staci C.; Saberi, Sima; Wheeler, Natalie C.; McDermott, Mollie; Hughes, Rebecca; et al.
Innovative strategies are needed to reduce the hypertension epidemic among African Americans. Reach Out was a faith-collaborative, mobile health, randomized, pilot intervention trial of four mobile health components to reduce high blood pressure (BP) compared to usual care. It was designed and tested within a community-based participatory research framework among African Americans recruited and randomized from churches in Flint, Michigan. The purpose of this pilot study was to assess the feasibility of the Reach Out processes. Feasibility was assessed by willingness to consent (acceptance of randomization), proportion of weeks participants texted their BP readings (intervention use), number lost to follow-up (retention), and responses to postintervention surveys and focus groups (acceptance of intervention). Of the 425 church members who underwent BP screening, 94 enrolled in the study and 73 (78%) completed the 6-month outcome assessment. Median age was 58 years, and 79% were women. Participants responded with their BPs on an average of 13.7 (SD = 10.7) weeks out of 26 weeks that the BP prompts were sent. All participants reported satisfaction with the intervention. Reach Out, a faith-collaborative, mobile health intervention was feasible. Further study of the efficacy of the intervention and additional mobile health strategies should be considered.